Azolla Pinnata SEGAR SEBAGAI PAKAN ALTERNATIF UNTUK MENGURANGI BIAYA PRODUKSI AYAM BROILER - Tarigan, Desriana Maya Sari; Manalu, Doni Sahat Tua (Jurnal AGRISEP, 2019)
Feeds costs are the largest cost in livestock business, which reaches 60-70% of all production costs. Feed costs can be reduced by using alternative feed ingredients that have high value, relatively cheap prices, easy to obtain and safe for consumption, and ones of its is Azolla pinnata. This study used a Completely Randomized Design (CRD) method with 5 (five) treatments and 4 (four) replications on 100 broilers. Each experimental unit is occupied by 5 (five) starter period broilers. The percentage of fresh Azolla pinnata in the ration of this experiment are; 0%, 5%, 10%, 15% and 20%. Broiler are maintained and retrieved data for 4 weeks. Parameters that observed were chicken weight, feed consumption and feed conversion. The results showed that the percentage of Azolla pinnata significantly affected the chicken weight and feed consumption, but the effect was not significant on feed conversion. The best use of fresh Azolla pinnata is at 10% level in the ration. Using azolla 10% in the ration can reduce the costs for commercial feed use up to  9.9% of total feed consumption.